A Case Study: Champion Photochemistry (M) Sdn Bhd - Gan, Boon Ting (1997)

(untitled)
The objectives of this case study is to appreciate the application of Statistical Process Control method and effective operation tools to facilitate the improvement of chemical processes in Champion Photochemistry (M) Sdn Bhd. The industry of photochemical is facing intense competition from all angles:- 1) Higher customer demand. 2) Technology change 3) Stiff competition 4) Short product life cycle. In this instance, in order to survive in the market place, continuous improvement activities and products innovative programs ia a necessity for the company.